Using the Weibull Distribution to Analyze the Reliability of Water Turbidity Removal and the Amount of Chlorine Remaining in the Water After Treatment - Jumaa Samih , Mohammed; Mahmoud Alwan, Iqbal (Journal of Economics and Administrative Sciences, 2024)
All water treatment centers in Iraq operate according to the standards specified in the legal regulations. Therefore, periodic evaluations must be conducted to study and analyze the quality of the outputs of these centers. The research used the two-parameter Weibull distribution to evaluate the reliability of turbidity removal and residual chlorine in the water at the Rashidiya water center in Baghdad, Iraq. The distribution parameters were estimated using the Maximum Likelihood method with the Matlab 2022 program, and the chi-square test for Goodness of Fit was used at a significant level of 0.05. The study found that the mean (and median = 9 NTU) of turbidity values were 9.47 NTU, which is within the permissible limit, and the mean (and median = 0.03 mg/L) of chlorine values were 0.0295 mg/L, much less than the permissible limit. The study also found that the average efficiency of turbidity removal was 72.179%, which is relatively acceptable, but needs improvement. The analysis showed that the value of reliability for the removal of turbidity was 0.99 ,and for the remaining amount of chlorine was 0.99, indicating that the Rashidiya water center was reliable during the study period. The study recommended several recommendations, the most important of which is the evaluation of all water treatment standards in the Rashidiya water center in particular and in all water treatment centers in Baghdad in general. Maintain continuous turbidity and chlorine levels monitoring to ensure compliance with permissible limits. Make efforts to improve the turbidity removal efficiency. Fostering collaboration between water treatment centers, researchers and regulatory agencies. Develop public awareness campaigns to educate the public on the importance of clean and safe water.